Risk prediction tools for older general surgical patients. Issue 1 (13th April 2015) - Middleton, M; Stechman, MJ; Moug, S; McCarthy, K; Hewitt, J
Summary This review identifies and examines the clinical application of risk prediction tools, including the American Society of Anaesthesiology (ASA) Classification System and POSSUM-based scores, in the older general surgical patient. Predicting outcomes in this patient group remains difficult; it is challenging to design a risk prediction tool that will apply to both emergency and elective surgery and that remains valid across the wide age range that this patient group encompasses. Risk prediction tools can have benefit but should be used in conjunction with the clinical assessment of those experienced in the care of this challenging patient group.